2019
DOI: 10.4209/aaqr.2019.06.0311
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Distribution of Particulate Matter and its Relationship with Planetary Boundary Layer Structure in Shenyang, Northeast China

Abstract: The impact of the planetary boundary layer (PBL) structure on the vertical distribution of aerosols in Northeast China, which experiences air pollution frequently in autumn and winter, is not well understood. We investigated the characteristics of the vertical distribution of particulate matter (PM 1 , PM 2.5 , and PM 10) mass concentrations and their relationships with PBL structures in Shenyang, a provincial capital city in Northeast China, using balloon sounding data collected during an intensive observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Research presenting impact of PBL dynamics, confirms that during convective conditions (mechanical and thermal turbulence) vertical distribution of PM concentrations is uniform (Li et al 2019;Strbova et al, 2017;Wang et al 2018). Mechanical turbulence can be caused by strong wind shear connected to LLJ (Li et al 2019), mountain waves (Zangl, 2003, hydraulic jump (Kishcha et al 2017), rotors (Kunin et al 2019) or passage of an atmospheric front. In the present study, wind shear turned out to be the most important factor in terms of PM10 vertical profile modification.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Research presenting impact of PBL dynamics, confirms that during convective conditions (mechanical and thermal turbulence) vertical distribution of PM concentrations is uniform (Li et al 2019;Strbova et al, 2017;Wang et al 2018). Mechanical turbulence can be caused by strong wind shear connected to LLJ (Li et al 2019), mountain waves (Zangl, 2003, hydraulic jump (Kishcha et al 2017), rotors (Kunin et al 2019) or passage of an atmospheric front. In the present study, wind shear turned out to be the most important factor in terms of PM10 vertical profile modification.…”
Section: Discussionsupporting
confidence: 54%
“…black carbon (Zhou et al, 2020) or organic PM10 tracers like levoglucosan (Marynowski et al, 2020). Numerous studies indicate that an important factor that affects the pollution profile is the wind profile (Li and Han, 2016;Zhou et al, 2020), occurrence of low-level jet (Li et al, 2012;Li et al, 2019) or downward flows of pollutants (Han et al, 2018) which may strongly modify diurnal cycle of a pollutant concentration at the lowest part of the troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also evidence of quite different results. The formation and evolution of air pollution episodes is influenced by wind speeds and wind shears caused by nocturnal low-level jets and cold fronts [ 29 ]. Moreover, the chemical production of sulphate, nitrate, and ammonium may increase due to the uplift of air pollutant together with humidity, which facilitates the heterogeneous and aqueous-phase oxidation of precursors [ 30 ].…”
Section: Macroscalementioning
confidence: 99%
“…Hu et al (2014) found that westerly warm advection above the Loess Plateau was transported over the NCP and imposed a thermal inversion, which acted as a lid and capped the pollution in the boundary layer (Xu et al, 2019). The dynamic structure of the PBL, including wind shears and turbulence, can modify air quality by influencing the dispersion and transport processes of air pollutants (Li et al, 2019). Zhang et al (2020) found that a much weaker vertical wind shear was observed in the lower part of the PBL under polluted conditions compared with that under clean conditions, which could be caused by the strong ground-level PM 2.5 accumulation induced by weak vertical mixing in the PBL.…”
Section: Introductionmentioning
confidence: 99%